FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA TENAGA HONORER BIDAN DI UPT PUSKESMAS LAMURUKUNG: FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA TENAGA HONORER BIDAN DI UPT PUSKESMAS LAMURUKUNG - Hasnidar (LPPM Institut Sains dan Kesehatan Bone, 2021)
Abstract. Amidwife is a women who has attended dan completed a midwifery education that has been recognized by the government and passed an examination in accordance with the applicable requirements, is recorded (registration), is legally given permission to practice. The purpose of this research isto know the factors that influence the performance of honorary midwifes. The research method isThis study was an analytic survey with a cross sectional design. This design is intended to identify the relationship between the independent variables of work interest, work environment, rewards, co-workers, motivation and attitudes with dependent variable of midwife honorary performance. So that the number of sample (total sampling) was determined as many 26 people.the results of research on honorary midwives at the technical implementation unit of the lamurukung health center in August-Septemberr showed that 19 midwives with good performance and 7 poor performance midwives. From the results of statistical tests showed the performance of the midwives pvalue 0,03, which is <0,05. Work environment pvalue=0,03 which is <0,05. Reward pvalue=0.02 which is <0,05. Co-workers pvalue=0,02 which is <0,05. Motivation pvalue=0,00 which is <0,05. Attitude pvalue=0,03 which is <0,05. This shows that there is a relationship between work interest, work environment, rewards, co-worker, motivation and attitude with the midwifes honorary performance.The conclusion of this research is there is a relationship between work interest, work environment, co-worker, rewards, motivation and attitudes with the midwifes honorary performance Abstrak. Bidan adalah seorang wanita yang telah mengikuti dan menyelesaikan pendidikan bidan yang telah diakui pemerintah dan lulus ujian sesuai dengan persyaratan yang telah berlaku, dicatat, (registrasi), diberi izin secara sah untuk menjalankan praktek. Tujuan penelitian ini adalah Diketahuinya Faktor-faktor yang mempengaruhi kinerja tenaga honorer bidan. Metode penelitian ini adalahPenelitian ini bersifat survey analitik dengan rancangan cross sectional. Rancangan ini dimaksudkan untuk melakukan identifikasi hubungan variabel independen minat kerja, Lingkungan kerja, imbalan, rekan kerja, motivasi dan sikap dengan variabel dependen kinerja honorer bidan. Sehingga ditentukan jumlah sampel (total sampling) yaitu sebanyak 26 orang. hasil penelitian pada tenaga honorer bidan di UPT Puskesmas Lamurukung pada bulan Agustus-September menunjukkan bahwa bidan yang memiliki kinerja yang baik sebanyak 19 orang dan yang memiliki kinerja yang kurang baik sebanyak 7 orang. Dari hasil uji statistik menunjukkan kinerja bidan nilai p value=0,03 yakni < 0,05. Lingkungan kerja nilai p value=0,03 yakni <0,05. imbalan nilai p value=0,02 yakni <0,05. Rekan kerja nilai p value=0,02 yakni <0,05. motivasi nilai p value=0,03 yakni <0,05. sikap nilai p value=0,03 yakni <0,05. Hal ini menunjukkan bahwa ada hubungan antara minat kerja, lingkungan kerja, imbalan rekan kerja, motivasi dan sikap dengan kinerja honorer bidan. Kesimpulanpenelitian ini adalah Ada hubungan antara minat kerja, lingkungan kerja, imbalan rekan kerja, motivasi dan sikap dengan kinerja honorer bidan